2020
DOI: 10.1177/2051415820932773
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre clinical evaluation of the safety and performance of a simple transperineal access system for prostate biopsies for suspected prostate cancer: The CAMbridge PROstate Biopsy DevicE (CamPROBE) study

Abstract: Objectives: To report the prospective multicentre clinical evaluation of a first-in-man disposable device, Cambridge Prostate Biopsy Device, to undertake local anaesthetic outpatient transperineal prostate biopsies. Material and methods: Disposable single-use Cambridge Prostate Biopsy devices were manufactured based on a previous prototype. The lead site developed a user training course and disseminated the method to other sites. The Cambridge Prostate Biopsy Device (CamPROBE) was offered as an alternative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…This study used transrectal biopsy to diagnose prostate cancer and these findings may not apply for transperineal biopsy, as a transperineal approach may provide superior access to the apical and anterior regions of the prostate. In addition, it has been shown that use of a transperineal approach results in a lower infection risk than a transrectal approach for prostate biopsy [37,38]. Similarly, MRI-visible lesions were not stratified on the basis of their zonal location within the prostate, which may have resulted in a better positive predictive value of MRI-targeted biopsy within certain prostate regions.…”
Section: Discussionmentioning
confidence: 99%
“…This study used transrectal biopsy to diagnose prostate cancer and these findings may not apply for transperineal biopsy, as a transperineal approach may provide superior access to the apical and anterior regions of the prostate. In addition, it has been shown that use of a transperineal approach results in a lower infection risk than a transrectal approach for prostate biopsy [37,38]. Similarly, MRI-visible lesions were not stratified on the basis of their zonal location within the prostate, which may have resulted in a better positive predictive value of MRI-targeted biopsy within certain prostate regions.…”
Section: Discussionmentioning
confidence: 99%
“…We developed a decision model comprising a decision tree with Markov models at the terminal nodes. Data informing the decision model were taken from a prospective case series representing the first rigorous data on the safety and acceptability of the CamPROBE [7], and other data from the literature to inform the likely cost effectiveness of the device, at various price points. We also conducted a value of information analysis (VoI) to guide the direction of further research to reduce uncertainty as to the cost effectiveness of TPUSBx devices.…”
Section: Methodsmentioning
confidence: 99%
“…These 'template biopsies' (making use of a grid placed over the perineum to guide needle insertion points) usually necessitate general anaesthesia (GA) with significant attendant costs. To overcome this, devices have been developed to permit transperineal biopsies (TPUSBx) to be performed under local anaesthesia (LA) and hence be more suited to the outpatient clinic setting [5][6][7]. To date however, it is not known how cost effective these devices are, especially given the relatively low cost and wide availability of the transrectal biopsy method.…”
Section: Modelled Clinical Diagnostic Pathway and Structurementioning
confidence: 99%
See 2 more Smart Citations